2012
DOI: 10.1111/j.1365-2125.2012.04320.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic profiling of a P2X7 receptor allosteric modulator GSK1482160 in healthy human subjects

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• P2X7 receptors are involved in the production of pro-inflammatory cytokines, such as Il-1b, by central and peripheral immune cells. Il-1b has been implicated as an important mediator of inflammation. Therefore, the P2X7 receptor is an attractive therapeutic target for inflammatory diseases. WHAT THIS STUDY ADDS• Findings in pharmacokinetics, pharmacodynamics, safety and tolerability of a P2X7 receptor modulator, GSK1482160, from the first human study for the molecule a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
76
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 19 publications
0
76
0
Order By: Relevance
“…Moreover, in isolated perfused rodent livers no evidence of hydroxylation has been shown, and in nearly all animal species studied most of the GSK14822160 parent was recovered from the urine (32). This is supported by the pharmacokinetic determination of the GSK14822160 clearance and circulating half-life, which when modeled are in excess of 2,177 mL/h and 30.5 h, respectively, in humans (derived from (32)).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Moreover, in isolated perfused rodent livers no evidence of hydroxylation has been shown, and in nearly all animal species studied most of the GSK14822160 parent was recovered from the urine (32). This is supported by the pharmacokinetic determination of the GSK14822160 clearance and circulating half-life, which when modeled are in excess of 2,177 mL/h and 30.5 h, respectively, in humans (derived from (32)).…”
Section: Discussionmentioning
confidence: 51%
“…Although the aforementioned tracer kinetic modeling was performed on metabolite-uncorrected data, which have been shown to affect interpretation of many PET radiopharmaceuticals (31), work on GSK1482160 in liver microsomes, liver S9 fraction, and hepatocytes in multiple species has been shown to be metabolically stable (32). Moreover, in isolated perfused rodent livers no evidence of hydroxylation has been shown, and in nearly all animal species studied most of the GSK14822160 parent was recovered from the urine (32).…”
Section: Discussionmentioning
confidence: 99%
“…The purinergic antagonists are being actively studied for their therapeutic potential and have been demonstrated to be safe in clinical trials testing P2X7 antagonists in the treatment of rheumatoid arthritis (including trials AZD9056, CE-224,535, and GSK1482160) (48)(49)(50)(51)(52). We postulate that the development of targeted therapies that block these signaling pathways may provide simultaneous treatment of HIV-1 infection, the chronic inflammation associated with HIV-1 infection, and, possibly, the associated long-term sequelae, including neurotoxic effects (53).…”
Section: Discussionmentioning
confidence: 99%
“…4,121 The trials for rheumatoid arthritis failed to show efficacy, but the trial of GSK1482160 95 showed a reduction of IL1b following exposure to LPS. 122 Antagonists of the P2X7R prevent neuronal apoptosis in the retina induced by ATP or by hypoxia. 118,[123][124][125][126]127,128 Such antagonists include Brilliant Blue G (BBG, structure not shown) and MRS 2540 91.…”
Section: P2xr Modulators As Drug Targets In the Eyementioning
confidence: 99%